The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1471-2164-13-602
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput novel microsatellite marker of faba bean via next generation sequencing

Abstract: BackgroundFaba bean (Vicia faba L.) is an important food legume crop, grown for human consumption globally including in China, Turkey, Egypt and Ethiopia. Although genetic gain has been made through conventional selection and breeding efforts, this could be substantially improved through the application of molecular methods. For this, a set of reliable molecular markers representative of the entire genome is required.ResultsA library with 125,559 putative SSR sequences was constructed and characterized for rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 37 publications
7
57
0
Order By: Relevance
“…These data were in agreement with previous analysis of Yang et al (2012) which revealed relationship between faba bean germplasm from diverse geographic origin using SSR markers. For some population (P19, P20 and P21), data showed incomplete relationship between the origin of the populations and the molecular clusters.…”
Section: Discussionsupporting
confidence: 93%
“…These data were in agreement with previous analysis of Yang et al (2012) which revealed relationship between faba bean germplasm from diverse geographic origin using SSR markers. For some population (P19, P20 and P21), data showed incomplete relationship between the origin of the populations and the molecular clusters.…”
Section: Discussionsupporting
confidence: 93%
“…For SSR development, approximately equivalent weights of 7-dayold leaves (15)(16)(17)(18)(19)(20) of each genotype were collected and pooled. Total genomic DNA was extracted using a cetyltrimethylammonium bromide (CTAB) method as modified by Edward et al [22].…”
Section: Category Numbersmentioning
confidence: 99%
“…454 GS-FLX technology (next-generation sequencing) provides new opportunities for microsatellite isolation due to its high throughput, low cost of operation, and more thorough representation of the genome [15,41]. To date, several crops have developed high-throughput and novel genomic SSR markers via 454 GS-FLX sequencing [18][19][20][21]42]. In this study, massively parallel sequencing technology was adopted and hoped to discovery numerous SSR with high quality from genome of broomcorn millet quickly.…”
Section: Development Of Microsatellite Markers Using 454 Pyrosequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 250,393 SSRs were identified from 247 faba bean accessions (Yang et al, 2012) using 454/FLX sequencing technology. Beyond providing SSR markers, these transcriptome assemblies have been used for identification of SNPs from NGS datasets generated from two or more genotypes (Table 2).…”
Section: Glyma07g05410/ Glyma16g01980mentioning
confidence: 99%